Description of Pelochrista cannatana sp.n. with notes on the Italian species of the genus Pelochrista Lederer, 1859 (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Italian tortricid moth, Pelochrista cannatana sp.n.from Sicilia, is described. Externally the new species resembles Pelochrista huebneriana(Zeller, 1846) and P. infidana (Hiibner, 1824). In male genitalia it issimilar to P. caecimaculana (Hiibner, 1796-99), the differences are small, seen inthe size of socius longer in P. cannatana, in neck of valvae more distinct in P.caecimaculana, in apex of sacculus less pronounced than in P. caecimaculana.The female genitalia of P. cannatana and P. caecimaculana are very similar toone another, the main differences are in ostium bursae, sterigma and corpus bursaemore developed in P. cannatana.Notes on 16 species of Pelochrista Lederer, 1859, of the Italian fauna are alsoreported.
Keywords: Lepidoptera Tortricidae; Pelochrista cannatana; new species; ltaly